CLOUD CULTURE: FLUID MEMORIES ON PLATFORM ENCLOSURES - Gekker, Alex (AoIR Selected Papers of Internet Research, 2021)
This paper brings together emerging work on the platformisation of cultural production (Nieborg and Poell 2018; Duffy, Poell, and Nieborg 2019) with (critical) approaches to digital archiving (Berry 2016; Brügger 2018; Ben-David 2019) and algorithmic curation (Noble 2018; Amoore 2020) to explore a proposed emerging ‘cloud culture’. The term encompasses (1) the technological capacity to modify cultural commodities after they have reached (and perhaps experience by) users; (2) the erosion of digital ownership, emblematic of similar trends in companies limiting one’s ability to modify – or even repair – their owned hardware and software; and (3) the data-driven race for content optimisation, where platform owners use consumer surveillance to deliver their products for maximum engagement (Helles and Flyverbom 2019). These three components of the term are further explored in relation to the ontological and epistemological repercussions of a continually updating cultural commodities, across four key domains. First, cloud culture highlights 2 . Second, it emphasises the 2 , and the shift of platform power toward large-scale cultural revisions. Third, it alerts over the seeming 2 of replaced and rewritten digital objects. Fourth and ultimately, this might have severe repercussions on 2 both for media researchers and – more importantly – the public at large